Rethinking pro-active disaster planning in the workplace: The case of a selected mine in Zimbabwe - Langtone Maunganidze; Farai Ncube; Peter Sibanda (Canadian Center of Science and Education, 2023)
In the history of the mining sector in Zimbabwe, one occupational disaster that evokes sad memories is the 6 June 1972 Kamandama incident at Hwange Colliery Company that claimed 427 miners. One of the challenges confronting the mining sector is capacity to prepare for such uncertainties and complexities. Events such as the rescue of trapped miners in Chile, and the recent Zimbabwean Platinum mine case in which 78 workers were trapped underground although successfully rescued are one of the few cases that have brought about a heightened global consciousness of the need for effective disaster and crisis management practices. This paper explores the nature and extent of the emergency or disaster preparedness of mining sector in Zimbabwe using the case of ABC mine’s (not its real name) experiences and practices. The study which is influenced by postmodernism, adopts a predominantly qualitative research design. It uses a mixture of both primary and secondary data. The paper’s central argument is that contemporary pro-active planning processes have limitations in as far as helping companies cope with the complex challenges such as disasters or emergencies. Emergencies and disasters are relatively ‘wicked’ problems which may only be managed by use of ‘post-normal’ planning strategies. In a world of such complex and shadowy possibilities organizations do not know if their strategies are appropriate or what consequences might be. The idea of ‘pro-active’ planning is a mirage that only serves to perpetuate the illusion that risk to workplace disasters is controllable or manageable. Overall, most of the prevention, response and post- recovery initiatives, are effectively managerial devices or representations to enhance the reputation of the organization.